Maxwell's understanding environmental health : how we live in the world - Falta, Deborah Alma (Burlington : Jones & Bartlett Learning, 2022)
'Maxwell's Environmental Health takes a unique approach to presenting Environmental Health. Rather than organizing topics around the traditional regulatory fields (air and water pollution, hazardous wastes, radiation, etc.), this book is structured around the choices we make as individuals and societies that result in environmental health hazards. Hence the subtitle:'How We Live in the World'--
Revision of: Understanding environmental health / Nancy Irwin Maxwell. 2nd ed. 2014.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 050
Keywords: Environmental health; Environmental health; Electronic books